(untitled) (Experimental biology, 2015)
As a result of biochemical studies of erythrocyte eluate revealed that metronidazole increased the adsorption of substances on the «old» red blood cells as compared with «young» erythrocytes. The results of fractionation of proteins by zone electrophoresis on cellulose acetate plate have been showed the increase in the concentrations of globulin fractions (alpha 1, alpha 2, beta and gamma) in the erythrocyte eluate on the «old» red blood cells